Utilization of coffee-flavored nata de coco in coffee jelly beverage - Tiong, Immaculate; Galvez, Flor Crisanta F. (2000.)
ABSTRACT Coffee flavored nata de coco was utilized in coffee jelly beverage instead of the usual gelatin. The study involved the selection of the standard recipe for coffee jelly beverage, determination of the best type of nata de coco and the size to use and consumer preference test on the coffee jelly beverage with gelatin and coffee-flavored nata de coco. The standard formulation for the coffee jelly drink that was used throughout the study was determined by doing preliminary tests. The use of the three types of nata (Type A, Type B, and Type C) produced coffee jelly beverages that were significantly different from one another at α=0.05. Considering the cost of nata, it was decided to use Type C (the cheapest) in subsequent studies that investigated on the appropriate size of the nata cubes for the beverage. Results indicated that the use of medium-sized (appropriately 1cm x 1cm) nata produced the most acceptable beverage. Consumer preference test showed no significant difference between coffee jelly beverage with coffee flavored nata de coco and that with gelatin.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Nata de coco; Beverages